Effect of sodium hypochlorite-based formulations on the adhesion interface after fiber post cementation - Costa, Joatan Lucas de Sousa Gomes; Manzoli, Tatiane Miranda [UNESP]; Besegato, João Felipe; Zaniboni, Joissi Ferrari [UNESP]; DE OLIVEIRA, Eliane Cristina Gulin [UNESP]; Galvani, Lucas David [UNESP]; Dantas, Andréa Abi Rached [UNESP]; Vaz, Luis Geraldo [UNESP]; Kuga, Milton Carlos [UNESP] (Japanese Society for Dental Materials and Devices, 2023)
The study evaluated the persistence of residues, bond strength and tags formation of a cementation system after post-space irrigation with different sodium hypochlorite-based irrigants. The groups were divided according to the irrigation protocol (DW: distilled water; SHS: sodium hypochlorite solution; SHG: sodium hypochlorite gel; and, SHT: sodium hypochlorite with surfactant). Forty roots (n=10) were used to evaluate the persistence of residues by scanning electron microscopy. Other forty roots were used to the push-out bond strength test, failure mode and tag formation analyses. Non-parametric data were submitted to Kruskal Wallis and Dunn tests, while parametric data were evaluated by one-way ANOVA. No difference was observed in the persistence of residues. DW showed the highest bond strength and tag formation. Type 2 failure mode was the most frequent in the experimental groups. Compared to control, SHT showed the best performance, since less negative effects on adhesive interface was observed.
Keywords: Adhesive systems; Bond strength; Fiber post; Sodium hypochlorite; Surfactant